Digital Transformation Based on Information Systems to Improve Public Service Quality: A Qualitative Study in Pangkalpinang City - Aditya Ahmad Fauzi; Sutari; Reni Artita; Intan Claradifa (Edusight International Journal of Multidisciplinary Studies, 2026)
Digital transformation has become a strategic priority in public sector reform, particularly in improving service quality and governance. This study aims to explore the role of information systems in enhancing public service quality in Pangkalpinang City using a qualitative approach. Data were collected through in-depth interviews, observation, and document analysis related to the implementation of Sistem Pemerintahan Berbasis Elektronik (SPBE). The findings indicate that system usability, service accessibility, and organizational readiness significantly influence service effectiveness. Furthermore, the study reveals that digital transformation improves transparency and promotes inclusive access to public services. However, challenges remain in system integration and digital literacy. This study contributes to the development of a conceptual model linking usability, accessibility, and institutional readiness to sustainable digital public services.